2010
DOI: 10.1111/j.1745-3992.2009.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard‐Setting Methods as Measurement Processes

Abstract: Some writers in the measurement literature have been skeptical of the meaningfulness of achievement standards and described the standard‐setting process as blatantly arbitrary. We argue that standard setting is more appropriately conceived of as a measurement process similar to student assessment. The construct being measured is the panelists' representation of student performance at the threshold of an achievement level. In the first section of this paper, we argue that standard setting is an example of stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…However, given the large number (4900) of unique panels generated for this study and the concordance with previous results generated from real data [ 33 ], it is reasonable to believe that the findings are generalizable. Moreover, as already explained, the assumptions made in the generation of the data are grounded in educational measurement and standard settings theories and findings in practice [ 12 , 29 , 32 , 35 , 47 , 67 ]. Note that as expected from a simulation study, this study measures the quality of a model rather than analysing any observed data [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the large number (4900) of unique panels generated for this study and the concordance with previous results generated from real data [ 33 ], it is reasonable to believe that the findings are generalizable. Moreover, as already explained, the assumptions made in the generation of the data are grounded in educational measurement and standard settings theories and findings in practice [ 12 , 29 , 32 , 35 , 47 , 67 ]. Note that as expected from a simulation study, this study measures the quality of a model rather than analysing any observed data [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Standard setting is an important aspect of assessment, with the literature describing a plethora of methods. Although each has unique features, most standard setting methods use panels of expert judges to determine the cut-scores between the different performance categories [ 4 , 5 , 14 , 47 , 50 ]. Among the judge-based standard setting methods, Angoff’s method (henceforth Angoff) and variants, have been used in a range of educational settings [ 2 , 4 , 13 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…The candidate's true level of ability will be above or below the categorisation threshold, it is just the decision makers who are uncertain. The individual candidate score and categorisation threshold score are estimates, as there is measurement error in both (Nichols et al 2010). So the difficulties in categorisation reflect the error in the difference between these two estimates.…”
Section: Dear Sirmentioning
confidence: 99%
“…If such data (the examinees’ ‘true’ ability) were available, there would be no need to set standards and cut-scores. Consequently, the quality of standard setting methods is commonly measured by the level of subjective agreement among judges, the reliability of the results, or the error of measurement of the yielded cut-scores [ 22 29 ].…”
Section: Introductionmentioning
confidence: 99%